Stages of change: Strategies to promote use of a Pediatric Early Warning System in resource-limited pediatric oncology centers - Woo, MC (2023)
Background: Pediatric Early Warning Systems (PEWS) assist early detection of clinical deterioration in hospitalized children with cancer. Relevant to successful PEWS implementation, the “stages of change” model characterizes stakeholder support for PEWS based on willingness and effort to adopt the new practice. Methods: At five resource-limited pediatric oncology centers in Latin America, semi-structured interviews were conducted with 71 hospital staff involved in PEWS implementation. Purposive sampling was used to select centers requiring variable time to complete PEWS implementation, with low-barrier centers (3–4 months) and high-barrier centers (10–11 months). Interviews were conducted in Spanish, professionally transcribed, and translated into English. Thematic content analysis explored “stage of change” with constant comparative analysis across stakeholder types and study sites. Results: Participants identified six interventions (training, incentives, participation, evidence, persuasion, and modeling) and two policies (environmental planning and mandates) as effective strategies used by implementation leaders to promote stakeholder progression through stages of change. Key approaches involved presentation of evidence demonstrating PEWS effectiveness, persuasion and incentives addressing specific stakeholder interests, enthusiastic individuals serving as models for others, and policies enforced by hospital directors facilitating habitual PEWS use. Effective engagement targeted hospital directors during early implementation phases to provide programmatic legitimacy for clinical staff. Conclusion: This study identifies strategies to promote adoption and maintained use of PEWS, highlighting the importance of tailoring implementation strategies to the motivations of each stakeholder type. These findings can guide efforts to implement PEWS and other evidence-based practices that improve childhood cancer outcomes in resource-limited hospitals. © 2023 The Authors. Cancer Medicine published by John Wiley & Sons Ltd.